ABCD open source software for managing ETD repositories. Issue 4 (3rd June 2014) - Namdev Dhamdhere, Sangeeta; De Smet, Egbert; Lihitkar, Ramdas
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to give technical information about the application of ABCD open source software for managing institutional repository of electronic theses and dissertations (ETDs) at various levels with illustrations. Design/methodology/approach – Practical method and programming in the ABCD software for building ETD repository and its management Findings – ABCD software is an excellent tool for creating institutional repository (IR) and manages it at various levels and to create ETD portal. Practical implications – The paper describes using ABCD software how one can create database of ETDs, how to submit ETDs in full text or abstract, how to search, how to implement it in open archive environment and simplicity of making union catalogue of ETD repositories on one platform of ABCD portal. Social implications – The process of ETD management and IR building using ABCD open source software will be useful to all the new institutions, colleges, universities, national libraries, international organizations who want to initiate the process of building ETD repository. Originality/value – The development team of ABCD software is still in process of releasing 2.0 versions and to develop tool for IR and ETD management. In this paper attempt has been made to describe with illustrations that how the software is making progress towards ETD management or building IR. One of the author is main project leader of ABCD open source software.